Nanostructured hexagonal ReO3 with oxygen vacancies for efficient electrocatalytic hydrogen generation. (11th June 2019) - Wu, Wenqi; Yao, Junjie; Liu, Shuyuan; Zhao, Liang; Xu, Li; Sun, Yinghui; Lou, Yanhui; Zhao, Jie; Choi, Jin-Ho; Jiang, Lin; Wang, Haibo; Zou, Guifu
Abstract: We report oxygen vacancies (OVs) rich hexagonal ReO3 nanostructured electrocatalysts for efficient hydrogen generation. Through a simple argon plasma exposure, OVs are introduced into the ReO3 nanoparticles (NP) and nanosheets to enhance electrocatalytic activities with decreasing overpotentails from 157 mV and 178 mV to 138 mV and 145 mV at the current density of 10 mA cm −2, respectively. As-processed OVs rich ReO3 NP exhibit a good stability during electrochemical measurements for 20 h in acidic electrolyte. The huge active surface area, abundant OVs and excellent conductivity contribute to the performance according to the experimental data. Further theoretical calculations show that the abundant OVs adsorb H with lower Gibbs free energy facilitating hydrogen evolution.